Music and Ideology: Musical School in Rezekne after World War II - Čakša, Valda (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of the article is to reflect the processes and problems of musical education renewal, which the teachers of Rezekne Secondary Music School faced under the circumstances of sovietisation, by evaluating to what extent the old elite (pre-war elite of National Conservatory) could adapt to the new circumstances and to what extent it was allowed by the regime. The article is based on the historical analysis of a discourse by evaluating the texts of documents available in the archives and identifying the dominant circumstances under which they have been created. In order to evaluate the principles of ideology influence and formation of social reality, the author compares the texts of the documents and conclusions found there with the opinions of representatives from various scientific areas on the features of musical life in that period of time. During the research, the author established that, on the one hand, the external factors and those, which are subjected to ideology, characterize the activity of the school; however, on the other hand, there are also the internal, as well as determined and retained factors of traditional requirements of music acquisition.